Analysis of Learning Module Effectiveness Self-Efficacy Review Oo Students with Visual Impairment - Arifin, Misbahul; Yusuf, Munawir; Subagya, Subagya (Universitas Sebelas Maret, 2023)
As a learning medium, modules undoubtedly possess an essential role in conveying information to students, with their characteristics of displaying more easily accepted information by students. This research, therefore, aims to analyze learning modules reviewed from self-efficacy for students with visual impairments. The research method employed is quantitative, with a quasi-experimental model, where two groups comprised experimental and control groups. The data collection technique used was a self-efficacy questionnaire, and the data were then analyzed utilizing descriptive statistics. This research examined 30 respondents who were students with visual impairments in class VII-IX SMP LB at SLB A YAAT Klaten and SLB A YKAB Surakarta. The research results revealed that the learning module used for students with visual impairments effectively increased student self-efficacy